Microsoft Silverlight 5 and Windows Azure enterprise integration : a step-by-step guide to creating and running scalable Silverlight enterprise applications on the Windows Azure platform - Burela, David (Enterprise : professional expertise distilled., 2012)
This book is a step-by-step tutorial that shows you how to obtain the necessary toolset to create and run Silverlight Enterprise Applications on Azure. The book also covers techniques, practical tips, hints, and tricks for Silverlight interactions with Azure. Each topic is written in an easy-to-read style, with a detailed explanation given and then practical step-by-step exercises with a strong emphasis on real-world relevance. If you are an application developer who wants to build and run Silverlight Enterprise applications using Azure storage, WCF Services, and ASP providers, then this book.